The effect of structural adjustment on African agriculture - Seck, Abdoulaye (Technical Centre for Agricultural and Rural Cooperation, 1991)
Papa Abdoulaye Seck is a computer scientist, economist and agriculturalist. For ten years his research has concentrated on fruit and vegetables. He is now the coordinator of the Institut Senegalais de Recherche Agronomlque (ISRA) research programme....